Penguatan Fungsi Keimigrasian Melalui Kerja Sama Pengawasan dan Optimalisasi SIMKIM: Urgensi Standar Operasional Prosedur Terhadap Penerjemah Asing Di Indonesia - Farrel Ahnaftama Suseno; Muhammad Azmi Fathoni; Muhammad Iqbal Anugrah (Jurnal Ilmiah Penegakan Hukum, 2026)
This study discusses the strengthening of immigration functions regarding the presence of foreign translators in Indonesia through cooperation in monitoring and optimizing the Immigration Management Information System (SIMKIM). Increased cross-border mobility has led to the widespread use of foreign translators in various sectors, such as business, health, education, and law enforcement. However, their presence also raises issues related to visa compliance, residence permits, reporting, and immigration supervision. This study uses a normative juridical method with a statutory, conceptual, and analytical approach. The legal materials used include immigration regulations, foreign worker employment regulations, and various journals and policy reports. The results show that Indonesia actually has a normative basis for monitoring foreigners through the immigration function, guarantor obligations, the Foreigner Monitoring Team, and SIMKIM. However, there is no standard operating procedure (SOP) that specifically regulates cooperation between law enforcement officers and users of foreign translator services. This condition results in suboptimal, non-uniform, and inadequately coordinated supervision. This article offers an ideal SOP construction that positions SIMKIM as a data integration node, establishes joint reporting obligations, differentiates regular and urgent procedures, and clarifies cross-agency follow-up mechanisms.